"Evaluating the 'reality' of South Africa's first season of Big Brother among a select group of Rhodes University students" - Pillay, Krivani (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2017)
This study analyses the reasons audiences watched South Africa's first reality television series, Big Brother, and sets out to determine which discourse of realism attracted audiences to the programme. The purpose of this study is to gain an understanding of the audience reception of South African reality television and to determine why audiences are attracted to this genre. The South African reality television programme, Big Brother, will be used as a case study to determine audience pleasures. This research also involves an examination of the 'reality' constructed by television producers and stakeholders. It will also investigate which discourse of realism viewers draw on when explaining the pleasures they obtain from watching Big Brother. What do audiences understand by the concept 'reality television'? Is there awareness of the fact that the series is highly constructed? This study outlines how the producers represent Big Brother and how they sell the programme as a reality television programme. This study also determines the producers' preferred meaning and sets out to reveal whether the audiences merely accept the producers' preferred reading of Big Brother. Audience ratings in the form of TAMS show that Big Brother is popular (Telmar; 2001). Fiske (1987) writes that in order for a television show to be popular, it has to be read and enjoyed by a diverse audience. Popular texts are polysemic in that their meanings can be inflected differently by various social groups watching the programme. This study examines how audiences understand the notion of reality television and if audience pleasures come from the myth that reality television represents reality.
Keywords: Uncatalogued